TINGKAT VARIASI GENDER POSISI MANAJEMEN PUNCAK DAN KUALITAS LABA PERUSAHAAN - Putriana Kristanti (Jurnal Riset Akuntansi dan Keuangan, 2010)
The purpose of this study is to analyze the relation of top management gender with  earnings management. This study analyzes a sample made of Jakarta stock exchange-listed firms. Three models used in this study, first model to measure the gender  variation, i.e. content analysis; the second model to analyze the earnings managemet,  with regression analysis; and the third model to examine the relation of top  management gender variation with earnings management, with corelation analysis. The  result show that top management gender variation is not correlated with earnings management. Keywords: top management gender, earnings management